Structural, electronic and optoelectronic properties of asymmetric organic ligands in Dion-Jacobson phase perovskites. (15th July 2022) - Zhang, Xiaoxiao; Xu, Ling; Chen, Mingyu; Kang, Yunxin; Lei, Jiayi; Wu, Qingyu; Sun, Chengshuai; Lin, Zhonghai; Wang, Pingjian; Yang, Zhi
Abstract: Dion-Jacobson (DJ) phase perovskites have attracted substantial attention in view of its showing great potential to solve the stability issue of optoelectronic devices. Herein, three organic ligands (1, 3-propanediamine PDA, N-methylpropane-1, 3-diammonium N-MPDA, and 3-(dimethylamino)-1-propylammonium DMPD) are selected as a spacer cation. The structural, electronic, and optoelectronic properties of organic ligands with different degrees of symmetry in n = 1 Dion-Jacobson (DJ) phase A'PbI4 (A' = PDA, N-MPDA, DMPD) perovskite are investigated by carrying out the first-principles method. The structural parameters show an increasing trend of crystal volume, octahedral distortion and stability of the crystal structure with the increase of ligand asymmetry. All three kinds of perovskites are direct bandgap semiconductors, and the bandgap values of A'PbI4 are in the order of N-MPDAPbI4 (2.711 eV) > PDAPbI4 (2.272 eV) > DMPDPbI4 (2.201 eV). The density of states (DOS) indicates that the 6p and 6s orbitals of Pb atoms and 5p orbitals of I atoms are mainly involved in conduction, while the contribution of organic ligands to electron orbitals is negligible. Additionally, the optoelectronic properties reveal that perovskite with asymmetric organic ligands has better absorption in the visible region than perovskite with symmetric organic ligands, which makes it useful as photovoltaic materials. The calculation of asymmetric organic ligands provides guidance and insights for the study of high-performance DJ phase perovskite. Highlights: The crystal volume, octahedral distortion, and structural stability increase with the degree of asymmetry. The band gap can be modulated by three organic ligands with varying degrees of symmetry. The asymmetric organic ligands have better absorption in the visible light region than with symmetric organic ligands.